Cytological status of Viola kitaibeliana (Section Melanium, Violaceae) in Europe - Magrini, Sara; Scoppola, Anna (Phytotaxa, 2015)
Viola kitaibeliana Schultes in Roemer & Schultes (1819: 383) was described for “Pannonia” as a small pansy with “caule erecto simplicissimo, foliis grosse crenatis, inferioribus subrotundis glabris, superioribus obovatis, stipulis similibus subintegerrimis, basive subpinnatis, petalo cornuto calycem glabrum aequante, reliquis brevioribus. Arvensi proxima, hac praecocior multo, (Aprili florens!) tenerior, et notis indicatis satis distincta. Flores 2, vel unicus, raro tres, oblique erecti in pedunculis folia excedentibus.” (Typus: M0112803; Fig. 1). Thereafter, many other names have been assigned to similar pansies described outside the Pannonian region: e.g. V. tricolor Linneus (1753: 935) var. nana De Candolle (1824: 304) and V. nemausensis Jordan (1846: 18) in France, V. tricolor subsp. minima Gaudin (1828: 210) in Switzerland, V. tricolor var. trimestris De Candolle (1824: 304), V. tricolor var. henriquesii Willk. ex Coutinho (1892: 36) and V. tricolor var. machadeana Coutinho (1892: 36) in the Iberian Peninsula. None of these taxa have been reported in Flora Europaea by Valentine et al. (1968) and later they have been included in V. kitaibeliana or placed in synonymy with it in the main floras (e.g. Muñoz Garmendia et al. 1993). According to Valentine et al. (1968) and to the updates of Magrini & Scoppola (2015b), in Europe V. kitaibeliana is widespread from Southwest to East, extending to Ukraine (Fig. 2).